Compreendendo os fenômenos nucleares, suas aplicações e implicações através de uma atividade lúdica - Martins, Gisela Garcia (2010)
It has been shown that students of latest high school year do not know the meaning of the symbols of radioactivity, and sometimes they mix up mentally with different sources of radioactivity or types of radiation. Students usually link radioactivity with nuclear weapons or with nuclear accidents that they have heard about. Important issues of radioisotopes such as the applications in medicine are unknown by students and seem to be far off student everyday life. Didactic and playful materials are recognized as important tools to help teachers to motivate students in many activities. In this work we have developed a didactic game for Chemistry and Physics students based on game approaches and new teaching/learning methods. The material proposed here consists in a ruleassisted didactic game, a board game with cards and dice that requires from the players the knowledge and reasoning in radioisotopes and nuclear phenomena to answer the proposed questions in order to get forward. This didactic game was tested in classroom and the results indicated an increase of student s interest and skills in the subject.